The Role of Teachers in Overcoming Student Delinquency in Grade VI Elementary School - Ivani Prihadi, Della; Latif, Latif (Universitas Negeri Semarang, 2024)
Widespread delinquency takes the form of breaking rules and making noise in the learning process in the classroom so that a teacher must be able to handle delinquency committed by students. This research aims to determine the forms of delinquency committed by students and the role of teachers in dealing with student delinquency at SD Negeri 19 Dayun. The research method used in this research is qualitative methods. Researchers used data collection techniques in the form of observation, interviews and documentation involving subjects, namely class VI teachers and class IV students at SD Negeri 19 Dayun. The data analysis technique in this research uses the Miles and Huberman model which consists of data reduction, data presentation and drawing conclusions. Based on the research results, it shows that there are several forms of student behavior such as chatting in class, being late for class, often making noise, cheating, being lazy about doing assignments, making fun of friends, bullying, damaging school property, truancy, violating school rules and regulations, etc. against the teacher. The role of the teacher in dealing with student delinquency is that the teacher becomes an example and the teacher becomes a guide by providing advice to students